Pengenalan Pembuatan Video Media Pembelajaran dengan Microsoft PowerPoint - Pungus, Stenly Richard; Sondakh, Debby Erce; Lengkong, Oktoverano; Sahulata, Reynoldus; Lontaan, Rolly; Tombeng, Marchel Thimoty (Servitium Smart Journal, 2024)
The Community Service activities that have been carried out at SD - SMP - SMA Madison School aim to introduce teachers, especially in making learning media videos where to attract students' interest in participating in learning is by using learning media. One of the most effective learning media is by using video. From the results of the pre-test, it was found that the teachers at Madison Scholl had used videos as learning media but many were still unable to make learning media videos so that the introduction to making learning media videos was very appropriate. The material provided is making learning media videos with Microsoft PowerPoint. Based on the results of the post-test, it was found that there was an increase in knowledge in making learning media videos.